1993
DOI: 10.1128/mcb.13.12.7935
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear RNase MRP is required for correct processing of pre-5.8S rRNA in Saccharomyces cerevisiae.

Abstract: RNase MRP is a site-specific ribonucleoprotein endoribonuclease that cleaves RNA from the mitochondrial origin of replication in a manner consistent with a role in priming leading-strand DNA synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
189
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(200 citation statements)
references
References 24 publications
9
189
2
Order By: Relevance
“…Assuming that the MRP3 and P3 hairpins in S. cerevisiae are functionally equivalent, we predicted that the reciprocal swap, the replacement of the P3 hairpin in P RNA with the MRP3 hairpin, would yield an active RNase P enzyme+ Therefore, we constructed a derivative of RPR1 (P-MRP3 Sc ) in which nt 32-85 of P RNA were replaced with the MRP3 hairpin (Fig+ 1)+ The remainder of RPR1, including flanking promoter and terminator regions, was unchanged+ However, in plasmid-swap experiments, this construct failed to complement either the ⌬rpr1 or the ⌬rrp2 mutations (Table 1)+ The RRP2 gene is reportedly transcribed by RNA polymerase II (Schmitt & Clayton, 1993b), whereas RPR1 is transcribed by RNA polymerase III (Allison & Hall, 1985)+ We surmised that the P-MRP3 Sc gene might not complement the ⌬rpr1 mutation because of the eight consecutive Us in the MRP3 sequence, which would be ignored by RNA polymerase II, but would serve as an efficient terminator for RNA polymerase III (Lee et al+, 1991)+ Therefore, we mutated the MRP3 sequence to eliminate the U 8 sequence by either replacing several bases in the U 8 run with As, or by deleting the entire U 8 sequence (see inserts in Fig+ 1)+ Both of these modified MRP3 hairpins were first used to replace the wild-type MRP3 hairpin in the MRP RNA gene (MRP-MRP3 U.A and MRP-MRP3 ⌬U )+ The resulting mutant MRP RNA genes were able to complement the ⌬rrp2 mutation, indicating that the U 8 sequence is not essential for RNase MRP activity (Table 1)+ We then replaced the P3 hairpin in the P RNA with the MRP3 U.A and MRP3 ⌬U sequences+ Both P-MRP3 U.A and P-MRP3 ⌬U genes complemented ⌬rpr1 (Table 1)+ As expected, RNA extracted from cells carrying the P-MRP3 mutant RNA genes did not include sequences that were hybridized by a P3-specific probe (Fig+ 2B, middle panel, lanes 2-5), but P RNA-and preP RNA-sized bands were detected with the MRP3-specific probe (Fig+ 2B, lower panel, lanes 2-5)+ Thus, the strains contain only the hybrid RNA and no wildtype P RNA+ To assess tRNA processing in the P-MRP3 mutant RNA strains, we probed the composition of valyl-tRNA+ We detected no accumulation of precursor valyl-tRNA with either of the mutated MRP3 replacements (Fig+ 2B, top panel, lanes 2-5)+ Furthermore, quantitation of the accumulation of P-MRP3 in either mutant strain using a probe specific for a region of P RNA outside the P3 hairpin indicated that the hybrid RNA accumulated to the same level as P RNA in wild-type strains (data not shown)+ Thus, RNase P containing either of the hybrid RNAs appears to have normal activity+ We conclude that, once the terminator-like sequence is removed, the MRP3 hairpin possesses the features necessary to replace P3 in P RNA+ Thus, the MRP3 and P3 hairpins are operationally equivalent+…”
Section: Replacement Of Hairpin P3 In P Rna By Hairpin Mrp3 From Mrp Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that the MRP3 and P3 hairpins in S. cerevisiae are functionally equivalent, we predicted that the reciprocal swap, the replacement of the P3 hairpin in P RNA with the MRP3 hairpin, would yield an active RNase P enzyme+ Therefore, we constructed a derivative of RPR1 (P-MRP3 Sc ) in which nt 32-85 of P RNA were replaced with the MRP3 hairpin (Fig+ 1)+ The remainder of RPR1, including flanking promoter and terminator regions, was unchanged+ However, in plasmid-swap experiments, this construct failed to complement either the ⌬rpr1 or the ⌬rrp2 mutations (Table 1)+ The RRP2 gene is reportedly transcribed by RNA polymerase II (Schmitt & Clayton, 1993b), whereas RPR1 is transcribed by RNA polymerase III (Allison & Hall, 1985)+ We surmised that the P-MRP3 Sc gene might not complement the ⌬rpr1 mutation because of the eight consecutive Us in the MRP3 sequence, which would be ignored by RNA polymerase II, but would serve as an efficient terminator for RNA polymerase III (Lee et al+, 1991)+ Therefore, we mutated the MRP3 sequence to eliminate the U 8 sequence by either replacing several bases in the U 8 run with As, or by deleting the entire U 8 sequence (see inserts in Fig+ 1)+ Both of these modified MRP3 hairpins were first used to replace the wild-type MRP3 hairpin in the MRP RNA gene (MRP-MRP3 U.A and MRP-MRP3 ⌬U )+ The resulting mutant MRP RNA genes were able to complement the ⌬rrp2 mutation, indicating that the U 8 sequence is not essential for RNase MRP activity (Table 1)+ We then replaced the P3 hairpin in the P RNA with the MRP3 U.A and MRP3 ⌬U sequences+ Both P-MRP3 U.A and P-MRP3 ⌬U genes complemented ⌬rpr1 (Table 1)+ As expected, RNA extracted from cells carrying the P-MRP3 mutant RNA genes did not include sequences that were hybridized by a P3-specific probe (Fig+ 2B, middle panel, lanes 2-5), but P RNA-and preP RNA-sized bands were detected with the MRP3-specific probe (Fig+ 2B, lower panel, lanes 2-5)+ Thus, the strains contain only the hybrid RNA and no wildtype P RNA+ To assess tRNA processing in the P-MRP3 mutant RNA strains, we probed the composition of valyl-tRNA+ We detected no accumulation of precursor valyl-tRNA with either of the mutated MRP3 replacements (Fig+ 2B, top panel, lanes 2-5)+ Furthermore, quantitation of the accumulation of P-MRP3 in either mutant strain using a probe specific for a region of P RNA outside the P3 hairpin indicated that the hybrid RNA accumulated to the same level as P RNA in wild-type strains (data not shown)+ Thus, RNase P containing either of the hybrid RNAs appears to have normal activity+ We conclude that, once the terminator-like sequence is removed, the MRP3 hairpin possesses the features necessary to replace P3 in P RNA+ Thus, the MRP3 and P3 hairpins are operationally equivalent+…”
Section: Replacement Of Hairpin P3 In P Rna By Hairpin Mrp3 From Mrp Rnamentioning
confidence: 99%
“…RNase MRP (mitochondrial RNA processing) was first identified as a ribonucleoprotein enzyme capable of in vitro formation of primers for mitochondrial DNA replication (Chang & Clayton, 1987;Schmitt & Clayton, 1992;)+ However, most of the enzyme is localized to the nucleolus (Reddy et al+, 1981;Reimer et al+, 1988;Kiss & Filipowicz, 1992), with only minute amounts found in the mitochondria (Topper et al+, 1992;Li et al+, 1994)+ Its cellular location suggested that the primary function of RNase MRP is in ribosome biogenesis+ Indeed, recent genetic evidence has established that RNase MRP is required for normal processing of 5+8S rRNA in Saccharomyces cerevisiae (Schmitt & Clayton, 1993b;Chu et al+, 1994;Lygerou et al+, 1994Lygerou et al+, , 1996+ The 5+8S rRNA of S. cerevisiae exists in short (5+8S S ) and long (5+8S L ) versions, differing by 6-7 nt at their 59 ends (Rubin, 1974;Lindahl et al+, 1992)+ The ratio of 5+8S S :5+8S L in wild-type cells is 5-10:1+ However, a single base change in the RNA subunit of RNase MRP results in a substantially decreased ratio of 5+8S S to 5+8S L , as well as accumulation of a very long version of 5+8S rRNA with 149 bases of the ITS1 sequence attached at the 59 end (Shuai & Warner, 1991;Lindahl et al+, 1992;Chu et al+, 1994)+ These observations together with other experiments (Henry et al+, 1994) have led to the conclusion that RNase MRP is responsible for initiating the processing of the short form of 5+8S rRNA by cleaving the pre-rRNA in the transcribed spacer between the 18S and 5+8S moieties+ RNase MRP is structurally related to RNase P, the endonucleolytic enzyme that creates the mature 59 end of tRNAs+ Both enzymes have one RNA subunit (here called MRP RNA and P RNA) that share secondarystructure features (Forster & Altman, 1990;Schmitt & Clayton, 1993a)+ Furthermore, RNases MRP and P of S. cerevisiae contain eight common protein subunits (Lygerou et al+, 1994;Chu et al+, 1997;Dichtl & Tollervey, 1997;Stolc & Altman, 1997;Chamberlain et al+, 1998;Stolc et al+, 1998); only one protein specific to each of the two nucleases has been identified (Schmitt & Clayton, 1994;…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the pre-rRNA processing occurs in the DFC+ Indeed, it has clearly been demonstrated that the DFC is rich in U3SnoRNA (PuvionDutilleul et al+, 1991)+ This RNA catalyzes the initial 59 external transcribed spacer processing and subsequent processing events around the 18 S region (Kass et al+, 1990;Savino & Gerbi, 1990;Hughes, 1996)+ Other snoRNAs, such as MRP and U8, which catalyze the processing within internal transcribed spacer I and at the 5+8S and 28S borders, respectively (Peculis & Steitz, 1993;Schmitt & Clayton, 1993;Chu et al+, 1994), have also been located in the DFC or in a subregion thereof (Reimer et al+, 1988;Matera et al+, 1994;Jacobson et al+, 1995)+ A fluorescent in situ hybridization analysis (Lazdins et al+, 1997), using probes for small selected segments of pre-rRNAs, which have known half-lives, has also revealed that the area of the DFC in which 39 ETS processing takes place is considerably smaller than that in which the 59 ETS processing occurs+ In the light of our present findings, it appears that the DFC could be subdivided into different functional subdomains that correlate with different steps of ribosome biogenesis+ First, the DFC directly surrounding FCs appears as an accumulation site, needed for BrUTP-RNA processing following its synthesis within the FC and its rapid migration from this compartment+ Second, the regions of the DFC that are not directly in contact with the FC are three-dimensionally structured as rings centered on the two latter components and functionally correspond to later steps of pre-rRNA processing+ Finally, the fourth labeling pattern, which is mainly located in the GC, appears as huge peripheral rings partially fused together, that surround the previous three other patterns+ The breaking of the more peripheral rings could suggest a disassembly of the GC before the spreading of preribosomal particles within the nucleoplasm+ The biological relevance of this finding with respect to later steps of rRNA export from the nucleolus toward the cytoplasm remains to be investigated+ Taken together, these different labeling patterns reveal distinct functional subdomains in which rRNAs are successively passing through+ As previously suggested (Lazdins et al+, 1997), it is clear that these domains are not strictly superimposed on nucleolar components identified by the presence of given proteins and snoRNAs or identified at the ultrastructural level+…”
Section: The Approach For Identifying Both Transcription and Processimentioning
confidence: 99%
“…In eukaryotic cells, three of the four mature rRNAs are formed from a polycistronic primary transcript by a complex, ordered series of endo-and exonucleolytic cleavages+ These cleavages remove the external (ETS) and internal (ITS) transcribed spacers from the transcript, leaving the mature 18S, 5+8S, and 25/28S rRNA molecules with precisely defined 59 and 39 ends+ The eukaryotic processing pathway has been most extensively characterized in the yeast Saccharomyces cerevisiae (Kressler et al+, 1999;Venema & Tollervey, 1999;Lafontaine & Tollervey, 2001; see Fig+ 1)+ In these cells, the first detectable intermediate is the 35S pre-rRNA, which has already lost most of the 39 ETS through cotranscriptional cleavage by Rnt1p (Abou-Elela et al+, 1996;Kufel et al+, 1999), the yeast homolog of bacterial RNase III+ The 35S precursor is cleaved endonucleolytically at sites A0, A1, and A2, resulting in a 39-extended 20S precursor to 18S rRNA and a 59-extended 27SA 2 precursor to 5+8S/25S rRNA that also still contains the complete ITS2, as well as a short remnant of the 39 ETS+ The mature 39 end of 18S rRNA is formed by endonucleolytic cleavage of 20S pre-rRNA at site D, which takes place in the cytoplasm (Stevens et al+, 1991;Moy & Silver, 1999;Vanrobays et al+, 2001)+ The major pathway for converting the 27SA 2 precursor into 5+8S and 25S rRNA starts with cleavage at site A3 by the endonuclease RNaseMRP (Schmitt & Clayton, 1993;Chu et al+, 1994;Lygerou et al+, 1996), followed by exonucleolytic digestion of the 27SA 3 precursor by exonucleases Xrn1p and Rat1p to site B1 S , the 59 end of mature 5+8S S rRNA (Henry et al+, 1994;Petfalski et al+, 1998)+ A minor pathway, starting with either the 27SA 2 or 27SA 3 intermediate, leads to 5+8S L rRNA, whose 59 end, located 6 nt upstream from B1 S , is probably the result of an endonucleolytic event+ The resulting two 27SB precursors are processed identically+ Cleavage at C2 within ITS2 results in formation of 7S and 25+5S pre-rRNA (Geerlings et al+, 2000)+ Maturation of the 7S precursor to 5+8S rRNA is a multistep process involving the exosome complex as well as the 39 r 59 exonucleases Rex1p and Rex2p (Mitchell et al+, 1996;Allmang et al+, 1999; Van Hoof et al+, 2000)+ Rex1p is also re-sponsible for the final stage of 39-end maturation of 25S rRNA, as well as formation of the mature 39 end of 5S rRNA (Van Hoof et al+, 2000)+ The 59 end of mature 25S rRNA again results from exonucleolytic digestion by Xrn1p and Rat1p that removes the remaining portion of ITS2 from the 25+5S pre-rRNA (Geerlings et al+, 2000)+ In the past decade, a multitude of nonribosomal, transacting factors has been identified that are crucial for correct and efficie...…”
Section: Introductionmentioning
confidence: 99%